Multicenter prospective study on multivariant diagnostics of autoimmune bullous dermatoses using the BIOCHIP technology - van Beek, Nina; Krüger, Stine; Fuhrmann, Tarek; Lemcke, Susanne; Goletz, Stephanie; Probst, Christian; Komorowski, Lars; Di Zenzo, Giovanni; Dmochowski, Marian; Drenovska, Kossara; Horn, Michael; Jedlickova, Hana; et al. (Journal of the American Academy of Dermatology, 2020)
BACKGROUND: The current standard in the serologic diagnosis of autoimmune bullous diseases (AIBD) is a multistep procedure sequentially applying different assays. In contrast, the BIOCHIP Mosaic technology combines multiple substrates for parallel analysis by indirect immunofluorescence. METHODS: Sera from 749 consecutive, prospectively recruited patients with direct immunofluorescence-positive AIBD from 13 international study centers were analyzed independently and blinded by using (1) a BIOCHIP Mosaic including primate esophagus, salt-split skin, rat bladder, monkey liver, monkey liver with serosa, recombinant BP180 NC16A, and gliadin GAF3X, as well as HEK293 cells expressing recombinant desmoglein 1, desmoglein 3, type VII collagen, and BP230 C-terminus and (2) the conventional multistep approach of the Department of Dermatology, University of Lübeck. RESULTS: In 731 of 749 sera (97.6%), specific autoantibodies could be detected with the BIOCHIP Mosaic, similar to the conventional procedure (725 cases, 96.8%). The Cohen κ for both serologic approaches ranged from 0.84 to 1.00. In 6.5% of sera, differences between the 2 approaches occurred and were mainly attributed to autoantigen fragments not present on the BIOCHIP Mosaic. LIMITATIONS: Laminin 332 and laminin γ1 are not represented on the BIOCHIP Mosaic. CONCLUSIONS: The BIOCHIP Mosaic is a standardized time- and serum-saving approach that further facilitates the serologic diagnosis of AIBD.
Keywords: dospělí; pemfigus; Female; dítě; Adult; Autoimmune Diseases; mladý dospělý; ženské pohlaví; Adolescent; fluorescenční protilátková technika nepřímá; lidé; Aged, 80 and over; autoimunitní nemoci; Pemphigus; prospektivní studie; Male; Pemphigoid, Bullous; Aged; Prospective Studies; Young Adult; bulózní pemfigoid; lidé středního věku; Child; senioři nad 80 let; senioři; mužské pohlaví; Fluorescent Antibody Technique, Indirect; Middle Aged; mladiství; Humans